Granulocyte-macrophage colony stimulating factor exacerbates collagen induced arthritis in mice. Issue 6 (1st June 1997) - Campbell, Ian K; Bendele, Alison; Smith, David A; Hamilton, John A
Abstract : OBJECTIVE: To examine the effect of granulocyte-macrophage colony stimulating factor (GM-CSF) on disease progression in the collagen induced arthritis (CIA) model in mice. METHODS: DBA/1 mice were primed for a suboptimal CIA response by intradermal injection of chick type II collagen without a secondary immunisation. Three weeks after immunisation the mice were given four to five consecutive daily intraperitoneal injections of recombinant murine GM-CSF (15 μg; 5 × 10 5 U), or vehicle, and arthritis development was monitored by clinical scoring of paws and calliper measurements of footpad swelling. At approximately six to eight weeks after immunisation mice were killed, their limbs removed and processed for histological analyses of joint pathology. RESULTS: Control animals receiving a single immunisation with collagen exhibited a varied CIA response both in terms of incidence and severity. Mice treated with GM-CSF at 20 to 25 days after immunisation with collagen had a consistently greater incidence and more rapid onset of disease than the vehicle treated control mice, based on clinical assessment. GM-CSF treated mice showed higher average clinical scores and greater paw swelling than controls. Histological analyses of joints reflected the clinical scores with GM-CSF treated mice displaying more pronounced pathology (synovitis, pannus formation, cartilage and bone damage) than control mice. CONCLUSION: GM-CSF is a potent accelerator of the pathological events leading to chronic inflammatory polyarthritis in murine CIA supporting the notion that GM-CSF may play a part in inflammatory polyarthritis, such as rheumatoid arthritis.